Die Entfremdung des Subjekts: Zur kritischen Theorie des Subjekts nach Pierre Bourdieu und Alfred Lorenzer - Wollenhaupt, Jonas (transcript, 2018)
The concept of alienation has returned. In this volume, it is theorized at the interface of sociology, social philosophy and social psychology.